Reader Response to Literary Political Discourse: A Critical Text World Theory Approach - Harbi, Raya (2021)
Readers’ spatial, temporal, and ideological positioning play an important role in readers’ responses toward literary political discourse (LPD) and how they identify with the text or its characters. This thesis uses the cognitive poetic framework, Text World Theory (TWT) (Werth, 1999; Gavins, 2007) with Critical Discourse Analysis (CDA) to account for the political discourses of the texts, the readers, and their contexts. TWT has been increasingly used among cognitive poetic researchers to account for readers’ emotional, cognitive and psychological projections (e.g., Lahey, 2005; Gavins, 2007; Stockwell, 2009; Whiteley, 2011; Canning, 2017). TWT has been adopted in this research with CDA to account for power relations in readers’ contexts and its impact on their responses and how they relate to such narratives. I, furthermore, investigate how power-relations in the actual world impact readers’ stances and positioning in and toward the text-worlds. Both the literary discourse and the reader responses are explored in light of context and the geopolitical background. As such investigation requires exploring different elements in the reading experience (e.g. text, style and context), a mixed approach was needed, hence, Critical Text World Theory (CTWT). This research pays special attention to readerly projection as a bidirectional process (Canning, 2017) and uses these projections as precursors to the reader’s positioning with regards to text and context. The texts in this thesis are selected to represent different periods, political themes and literary genres, featuring a dystopian novel (Orwell’s 1984), a pair of Palestinian/Israeli poems (“Shades of Anger” and “Woman Martyr”), and a philosophical parable (Le Guin’s “The Ones Who Walk Away from Omelas). The thesis uses a mixed method approach and draws upon both naturalistic reader response data as well as semi-structured interviews and a focus group. The original CTWT analysis in this thesis offers valuable insight into how power relations in the readers’ spaces manifest differently in their responses and how text, context, and the reader are closely interconnected.